KAJIAN FILOSOFI TRADISI NAWUR PENEMPUH PADA UPACARA PERKAWINAN DI DESA ADAT SELAT PANDAN BANTEN KECAMATAN SUKASADA, KABUPATEN BULELENG - Ni Putu Ayu Dian Puspa Wijayantini; I Putu Ariyasa Darmawan; Ketut Agus Nova (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2023)
Nawur penempuh is a continuation ceremony at the wedding ceremony, Based on this background, the following problems are formulated: 1) What is the basis for the existence of the Nawur Penempuh Tradition at the wedding ceremony in the Selat Pandan Traditional Village, Banten, 2) What is the function of the Nawur Penempuh Tradition at the wedding ceremony in the Selat Pandan Traditional Village, Banten, 3) What is the meaning of philosophy contained in the Nawur Penempuh Tradition at the wedding ceremony in the Selat Pandan Traditional Village, Banten. The basis for the Nawur Penempuh tradition is as follows: 1) History of the Nawur Penempuh tradition, 2) Religious foundation, 3)Place of implementation of the Nawur Penempuh, 4) Time of implementation of the Nawur Penempuh, 5) Stages of the implementation of the Nawur Penempuh, 6) Means of Nawur Penempuh ceremonies, 7) Prayers and spells of Nawur Penempuh performers. The functions of the nawur traveler tradition are: 1) The function of offering theology and devotional service to prostrate gratitude for the gifts that have been given, 2) The function of togetherness in the nawur traveler tradition can be seen in the togetherness that is created between the outside and local communities mutually forming a sense of togetherness between society, and 3) The symbolic function of paying the Nawur Penempuh is found in the male suckling pig which is an important requirement in the Nawur Penempuh tradition because it is the content of the bhisama and if not the male suckling pig is offered then the offering given is abstractly not accepted and is called kepindon Meaning The philosophy contained in the nawur penempuh tradition: The meaning of cultural preservation is to preserve cultural customs. The second meaning is ethics regarding controlling the minds possessed by the community during the implementation of the nawur penempuh ceremony so that the sanctity and sacredness of the event is maintained from beginning to end which is carried out in a solemn manner. Keywords : Philosophy, Nawur Penempuh Tradition